Chemical and Mineralogical Characterization of Biomass Ashes for Soil Reinforcement and Liner Material - Studart, André; Marchiori, Leonardo; Vitoria Morais, Maria; Albuquerque, António; Gabriel Almeida, Pedro; Cavaleiro, Victor (KnE Materials Science, 2022)
Mineralogical and chemical evaluations are necessary to investigate the background and origins of materials. In terms of residues commonly produced around the world, ashes biomass stands out for its high calorific capacity and use for energy production at thermoelectrical facilities. Given current sustainability issues and new demands from society, ashes and soil from pine biomass in the Castelo Branco region were investigated to research possible anthropogenic contaminations, heavy metals among their composition, and their physic-chemical characteristics. These properties can be used to define possible valorisation methods through residue introduction into the soil for its reinforcement and liner application. The results indicated that ashes biomass could help achieve these objectives and could be introduced into the soil, due to its enrichment with pozzolanic minerals and fine granulometry, while having a low-density, which could reduce final weight; however it was considerably different from the original biomass, and contained anthropogenic contaminations and high concentrations of heavy metals. Keywords: biomass ashes, chemical and mineralogical properties, residue valorisation, soil reinforcement, liner material